Comparative Phenotypic and Agronomic Assessment of Transgenic Potato with 3R-Gene Stack with Complete Resistance to Late Blight Disease - Byarugaba, A.A.; Baguma, G.; Jjemba, D.M.; Faith, A.K.; Wasukira, A.; Magembe, E.; Njoroge, A.W.; Barekye, A.; Ghislain, M. (MDPI, 2021)
Transgenic potato event Vic.172, expressing three naturally occurring resistance genes (R genes) conferring complete protection against late blight disease, was evaluated for resistance to late blight, phenotypic characterization, and agronomic performance in field conditions at three locations during three seasons in Uganda. These trials were conducted by comparison to the variety Victoria from which Vic.172 derives, using identical fungicide treatment, except when evaluating disease resistance. During all seasons, the transgenic event Vic.172 was confirmed to have complete resistance to late blight disease, whereas Victoria plants were completely dead by 60–80 days after planting. Tubers from Vic.172 were completely resistant to LB after artificial inoculation. The phenotypic characterization included observations of the characteristics and development of the stems, leaves, flowers, and tubers. Differences in phenotypic parameters between Vic.172 and Victoria were not statistically significant across locations and seasons. The agronomic performance observations covered sprouting, emergence, vigor, foliage growth, and yield. Differences in agronomic performance were not statistically significant except for marketable yield in one location under high productivity conditions. However, yield variation across locations and seasons was not statistically significant, but was influenced by the environment. Hence, the results of the comparative assessment of the phenotype and agronomic performance revealed that transgenic event Vic.172 did not present biologically significant differences in comparison to the variety Victoria it derives from.